Influence of Surface Morphology and Titanium Oxide Film Thickness on Its Photo-Electrochemical Properties - A. Seitmagzimov, Altay; M. Seitmagzimova, Galina; K. Bishimbayev, Valikhan (Asian Journal of Chemistry, 2013)
The goal of investigation is to determine the influence of porous structure of anodic titanium oxide on its photoelectrochemical properties. Results showed that within a certain thickness of tubular porous layer (from 300 nm and up) photocurrents can surge, mainly being dependent on electrophysical parameters of titanium oxide layer. After prolonged anodization of titanium (more than 3 h) in sulphuric acid electrolyte with added ammonium fluoride tubular structure of titanium oxide film changes into globular, which leads to a sharp change in photoelectrochemical characteristics-a more than twofold increase in photocurrent. It was concluded that ideally the electrode for photoelectrolysis of water must have minimum thickness with maximum possible porosity.